Role of Artificial Intelligence in Cybersecurity Improvement: Muhammad Shairoze Malik - Muhammad Shairoze Malik (International Journal for Electronic Crime Investigation, 2021)
In recent years, the importance of cyber security and personal privacy protection has increased significantly. To protect computer systems from attacks several solutions have been proposed by researchers and many cybersecurity tools have been developed. However, with the increase in the complexity of hacking attempts, the old traditional ways to counter malware cannot be relied upon. This paper introduces the need for the development of innovative cybersecurity skills and how many security systems like Intrusion Detection Systems (IDS) can be improved using Artificial Intelligence (AI). AI is used by nearly every company around the world to optimize and enhance their system's safety. In this paper, advanced cybersecurity solutions for intrusion detection systems enhanced with the use of artificial intelligence are discussed. The advantages and disadvantages of existing methods are explained and some promising future directions are also discussed.